The Saturday Night Supper Club - Laureano, Carla (A supper club novel, 2018)
Denver chef Rachel Bishop won a James Beard Award and heads up her own fine-dining restaurant-- until she is the target of a smear campaign. Alex Kanin was highlighting the pitfalls of online criticism-- and destroyed the career of a perfect stranger. Plagued by guilt, he agrees to help rebuild Rachel's tarnished image by offering his connections and his home to host an exclusive pop-up dinner party targeted to the Saturday Night Supper Club. As they work together to make the project a success, can Rachel give up her lifelong goals without losing her identity as well?